Determinants of Stock Investment Decisions Among Indonesian University Students: Examining the Role of Peer Influence and Financial Literacy Through the Mediating Effect of Risk Tolerance - Muhammad Ajis; Siti Aisyah Hidayati; Lalu Hamdani Husnan (Al-Kharaj: Journal of Islamic Economic and Business, 2026)
The purpose of this study is to analyze the determinants of stock investment decisions among undergraduate students in Indonesia, with risk tolerance serving as a mediating variable. Despite the exponential growth of young investors reaching 20.32 million Single Investor Identification (SID) by 2025, with more than 52% under the age of 30 the quality of investment decision-making among this cohort remains underexplored, particularly with respect to the psychological mechanisms that bridge cognitive and social influences. Using a quantitative associative-causal design, data were collected from 141 active undergraduate students who hold verified securities accounts and actively trade stocks, selected through purposive sampling. Structural Equation Modeling with Partial Least Squares (SEM-PLS) was employed for analysis. The findings reveal that financial literacy exerts a strong direct positive effect on stock investment decisions and on risk tolerance. Peer influence demonstrates no direct effect on investment decisionS, but exerts a significant indirect effect fully mediated by risk tolerance (full mediation). Risk tolerance itself is a significant determinant of investment decisions, and partially mediates the relationship between financial literacy and investment decisions (complementary mediation). These results confirm that investment decisions among students are the product of a complex integration of cognitive, social, and psychological factors. The study contributes theoretically by integrating Theory of Planned Behavior, Financial Socialization Theory, and Prospect Theory into a unified behavioral finance model for young investors.